2005
DOI: 10.1111/j.1523-1755.2005.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dry weight by monitoring changes in blood volume during hemodialysis using Crit-Line

Abstract: Determination of the extent of both intradialytic decreases in blood volume and postdialytic vascular compartment refill, combined with clinical assessment of intradialytic hypovolemia and postdialytic fatigue, can help assess patient dry weight and optimize volume status while reducing dialysis associated morbidity. The number of hospital admissions due to fluid overload may be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 24 publications
4
72
2
Order By: Relevance
“…A technique that may help attain better control of volume status is continuous noninvasive monitoring of the hematocrit (NIVM). NIVM has been proposed as a more accurate method of estimating the dry weight in both adults and children (11)(12)(13)(14). An NIVM-directed ultrafiltration (UF) algorithm was believed to reduce the hospitalization rate for severe fluid overload in a pediatric HD population at a single center, although the patients studied had already been receiving NIVM before the algorithm was introduced in that dialysis unit (15).…”
mentioning
confidence: 99%
“…A technique that may help attain better control of volume status is continuous noninvasive monitoring of the hematocrit (NIVM). NIVM has been proposed as a more accurate method of estimating the dry weight in both adults and children (11)(12)(13)(14). An NIVM-directed ultrafiltration (UF) algorithm was believed to reduce the hospitalization rate for severe fluid overload in a pediatric HD population at a single center, although the patients studied had already been receiving NIVM before the algorithm was introduced in that dialysis unit (15).…”
mentioning
confidence: 99%
“…Rodriguez et al (78) demonstrated that in patients in whom BVM remained stable, more fluid could be removed during a dialysis session than in patients with steep decrease of BV; however, this study reflects only the clinical reality that some patients do and others do not tolerate ultrafiltration and that the latter tend to end up fluid overloaded. Tools allowing BVM have been included in several dialysis monitors and coupled online with biofeedback systems to devices, thereby modifying elements of the dialysis strategy.…”
Section: Assessment Of Fluid Status and Body Compositionmentioning
confidence: 43%
“…Studies among hemodialysis patients in adults and children suggest that managing intradialytic RPV may reduce the number of hospital admissions due to fluid overload (14,19), improve BP control, and decrease hypotension-associated dialysis symptoms (20). It is possible that the latter benefit is, in part, related to diminished use of antihypertensive medication.…”
Section: Dry-weight and Outcomesmentioning
confidence: 99%
“…Thus, RPV slope monitoring may be useful to assess dry-weight among hypertensive hemodialysis patients. RPV monitoring, combined with clinical assessment of intradialytic hypovolemia and postdialytic fatigue, can help assess patient dry-weight and optimize volume status while reducing dialysis-associated morbidity (14). Wabel et al (15) measured body composition through body impedance analysis and predialysis systolic BP among 500 patients from eight dialysis centers in Europe.…”
Section: Newer Developments In the Assessment Of Dry-weightmentioning
confidence: 99%